Radiation Emergency Readiness Among US Medical Toxicologists: A Survey. (20th June 2021) - Murray, Brian P.; Kim, Eungjae; Ralston, Samuel A.; Moran, Tim P.; Iddins, Carol; Kazzi, Ziad
ABSTRACT: Introduction: Large scale radiologic and nuclear disasters are rare; however, recent events such as the Fukushima Daiichi nuclear reactor emergency in Japan and current global political tensions have highlighted the need for health-care providers with expertise in managing radiation injuries. Medical Toxicologists have the ability to collaborate with other specialists in filling this critical role. Methods: We conducted a cross-sectional survey to assess the attitudes, experiences, and knowledge of medical toxicologists through the assistance of the American College of Medical Toxicology. Results: The survey was completed by 114 medical toxicologists during the enrollment period. Medical toxicologists who had a willingness to participate in radiologic or nuclear emergencies or who had taken care of patients contaminated with radioactive material were more likely to perform well on the knowledge assessment. Conclusion: We identified that there is a group of medical toxicologists who have the willingness, experience, and knowledge to help manage patients in the event of a radiologic or nuclear emergency.